Penerapan Living Value Education melalui Kegiatan Keagamaan di Sekolah Dasar Swasta Provinsi Papua Barat Daya - Islami, Mukhamad Averros Azzam Al; Hidayat, Nur; Handayanti, Lestari (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Living Value Education is an educational approach that encourages the formation of good attitudes and behavior so that they become habits and later these habits can revive life values. The aim of this research is to determine the implementation of Living Values Education through religious activities carried out in elementary schools in Southwest Papua Province, along with supporting and inhibiting factors. The research method used is a qualitative approach with a descriptive type. The results of the research show that there are six Living Value Education values that are implemented through religious activities in the Southwest Papua Provincial Private Elementary School, namely religion, honesty, humility, cooperation, responsibility and tolerance. There are two supporting factors, namely, support from the school community and having sufficient gazebo facilities. Meanwhile, the inhibiting factors and solutions are that there are several students who are still late when praying in congregation. The solution is for the teacher to accompany them from behind so that other students are not as solemn in praying and the teacher scolds students who are still playing while praying. Second, the lack of space in the gazebo is not enough to accommodate all students for prayer. Solution: Congregational prayer is divided into two, where some students pray in the classroom and some pray in the gazebo.